Physiological and Genetic Variations of Amorphophallus variabilis in Bojonegoro based on Glucomannan Content, Calcium Oxalate and RAPD Markers - Pambudi, Achmad Yogi; Harijati, Nunung; Arumingtyas, Estri Laras (Graduate School, Universitas Brawijaya, 2020)
This study had purpose to determine the glucomannan and calcium oxalate content in 7 variants of A. variabilis and their genetic relationships based on RAPD markers. Amorphophallus variabilis Tuber samples were taken from Karangdowo village, Sumberrejo Sub-district, Bojonegoro District, East Java. Each variant was analyzed for its glucomannan content by the spectrophotometric method using 3,5-DNS reagents and calcium oxalate by the 0.1N KMnO4 titration method. Leaf DNA extraction was carried out using the CTAB method. Relationship analysis used RAPD markers with 5 primers (OPA-11, OPC-04, OPU-06, OPC-07, and OPN-1). The obtained data were analyzed using the Numerical Taxonomy and Multivariate System (NTSYS-pc) version 2.1. The grouping of glucomannan content or oxalium oxalate used hierarchical clustering analysis (SPSS 16.0). This research found that the calcium oxalate content in seven variants of A. variabilis ranged from 0.01 to 0.03 g, where the variant with the lowest calcium oxalate is V6 with a value of 0.01 g and the highest is the V7 variant with a value of 0.03 g, while the glucomannan content ranges from 9 - 38%. The highest glucomannan content is V3, while the lowest is V6. Phenograms formed based on RAPD markers showed the formation of two groups of A. variabilis. Group one has two subgroups. Subgroup one consists of variants V1 and V4, while subgroup two consists of V6 and V7. Meanwhile, the second group consists of variants V2, V3, and V5. The seven variant grouping pattern of A. variabilis based on RAPD markers has no similarity to the grouping pattern based on the results of glucomannan or calcium oxalate analysis.